Thermokinetic Characteristics of Jurassic Coal Spontaneous Combustion Based on Thermogravimetric Analysis. Issue 8 (11th June 2022) - Zhang, Duo; Wang, Weifeng; Deng, Jun; Wen, Hu; Zhai, Xiaowei; Shu, Chi-Min
ABSTRACT: To prevent coal fire disaster, a precision grading warning method was previously proposed for coal seams that are susceptible to spontaneous combustion. The uncertainty in the reaction mechanism of the spontaneous combustion of coal greatly restrains the in-depth understanding of the fine division theory in the course of coal combustion. In this paper, further research has been conducted to study the mechanism of this method. In this study, thermogravimetric analysis was carried out on the Jurassic coal of three different metamorphic grades. The variations of the TG/DTG curves of the coal samples at four heating rates were compared to examine their kinetic model and kinetic compensation effect. For the three samples of the Jurassic coal, a similar trend was obtained for the TG and DTG curves at the different heating rates. With an increase in the heating rate, the hysteresis phenomenon appeared in the TG/DTG curves. In the low-temperature coal oxidation stage, the most probable mechanism function of Coal A and Coal B was obtained to be No.9 ( G (α) = [1-(1-α) 1/2 ] 2, f (α) = (1-α) 1/2 [1-(1-α) 1/2 ] −1 ), and that of Coal C was No.14 ( G (α) = [-ln(1-α)] 2, f (α) = (1-α)[-ln(1-α)] −1 /2). A significant kinetic compensation effect was also observed in the oxidation stage. Despite the difference in the metamorphic grade, the reaction process of the low-temperature oxidation, as well as the rate-determining step was the same for the three samples.